NGHIÊN CỨU HOẠT TÍNH ESTROGEN CỦA CÁC ISOFLAVON CHIẾT XUẤT TỪ PHÔI HẠT ĐẬU TƯƠNG - Lê, Minh Châu; Đỗ, Thị Hoa Viên; Hồ, Phú Hà (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON ESTROGENIC ACTIVITY OF ISOFLAVONE EXTRACTS FROM SOY GERMThis study was performed to evaluate the effect of isoflavones extracted from soy germ on menopausal symptoms associated with 4-vinyl cyclohexene diepoxide (VCD)-induced follicular failure in mice. Total isoflavone extract (CE) and aglycone-enriched extract (TPCa) from soybean embryos 50 mg/kg/day were both able to improve female physiological characteristics positively. The CE sample was able to slightly increase the uterine volume (p<0.001), increase the number of primary follicles (p<0.001), and increase the estradiol content (p<0.001). TPCa sample also can slightly increase uterine volume (p<0.05), increase the number of primary follicles (p<0.001), and increase estradiol content (p<0.001). These results suggest the potential for using isoflavones from soybean embryos in the prevention and treatment of menopausal symptoms - more effectively and safely than traditional hormone therapy.